2017
DOI: 10.1088/1367-2630/aa936a
|View full text |Cite
|
Sign up to set email alerts
|

Opinion competition dynamics on multiplex networks

Abstract: Multilayer and multiplex networks represent a good proxy for the description of social phenomena where social structure is important and can have different origins. Here, we propose a model of opinion competition where individuals are organized according to two different structures in two layers. Agents exchange opinions according to the Abrams-Strogatz model in each layer separately and opinions can be copied across layers by the same individual. In each layer a different opinion is dominant, so each layer ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…This model gives binary states to a node and each time a randomly chosen node updates its opinion into that of its randomly chosen neighbor. The voter model-type processes were studied in the multilayer network perspective [19,20], in which individuals tend to maintain the same opinion in different layers through interlayer links. It was found that there could be coexistence phase of two states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This model gives binary states to a node and each time a randomly chosen node updates its opinion into that of its randomly chosen neighbor. The voter model-type processes were studied in the multilayer network perspective [19,20], in which individuals tend to maintain the same opinion in different layers through interlayer links. It was found that there could be coexistence phase of two states.…”
Section: Introductionmentioning
confidence: 99%
“…Also shown is the result of KGS model of[27]. Simulations are done with networks of N=10 5 and with MC time steps of t final =2 16 -220 . Both the symbols and the connecting lines are the Monte Carlo simulation results.…”
mentioning
confidence: 99%
“…Multilayer networks are a framework not only for a better description of complex systems but also for novel dynamical processes that cannot be captured in a single layer framework [9,[13][14][15]. Indeed, several studies on multilayer networks show that interlayer connections account for significant differences in many phenomena, including percolation [10,16,17], diffusion [18], epidemic spreading [19][20][21][22], cascade of failures [11,23], opinion formation [15,[24][25][26], online communities [27], game theory [28][29][30] or cultural dynamics [31].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, adapting the network topology has also successfully been used to control cluster synchronization in delay-coupled networks [34].Another focus of recent research in network science are multilayer networks, which are systems interconnected through different types of links [35][36][37][38]. A prominent example are social networks which can be described as groups of people with different patterns of contacts or interactions between them [39][40][41]. Other applications are communication, supply, and transportation networks, for instance power grids, subway networks, or airtraffic networks [42].…”
mentioning
confidence: 99%